Diferencias planeadas: la Asignación Universal por Hijo en Argentina desde una perspectiva de derechos humanos - Horacio Javier Etchichury (Universidad Hemisferios, 2018)
This article intends to analyze Universal Child Allowance (UCA)—a large-scale conditional cash transfer (CCT) program in Argentina—from a human rights and constitutional perspective. Conditions required in the UCA system—which covers informal and unemployed workers—are compared to those established in family allowances, the contributory program created for registered workers. These differences in treatment are analyzed in connection with the right to equal treatment, taking into account applicable legal materials, including caselaw and theoretical contributions. After describing CCT programs in general and the specific features of UCA, and outlining Argentina’s constitutional and human rights framework, the article describes the specific conditions—maximum income, nationality, maximum number of covered children—applied only to informal and unregistered workers included in the UCA program. Compared to family allowances beneficiaries, workers under UCA have a much lower maximum wage limit to be eligible, and their children must fulfill nationality or legal residence requirements not applicable under the family allowances system. UCA covers only up to five children per family, while family allowances are paid to every child in formal workers’ families, with no restrictions. The article concludes that these planned differences in treatment are not admissible under Argentina’s human rights obligations and constitutional setting. The article also advocates a human rights-based design for social policies, in order to ensure consistency with Argentina’s Constitution and international obligations.